Transudative chylothorax in a liver cirrhosis patient: A case report. (2022) - Nganga, Rose; Pulliam, Christian; Sessions, William; Stola, Amber; Gregg, Justin
Abstract: Chylothorax defines chyle in the pleural space, usually from defects in thoracic duct. Chylothoraces are usually exudative, as defined by light's criteria but in rare instances, chylothoraces can be transudative. The leading cause of non-traumatic chylothorax is malignancy, but a non-traumatic chylothorax can be a rare manifestation of liver cirrhosis. In this case report, we present a case of an 82-year-old male with a history of non-alcoholic liver cirrhosis requiring multiple paracenteses for chylous ascites in the past, who was found to have a transudative non-traumatic chylothorax. His chylothorax existed despite his ascites being resolved for over a year. We will describe this case of a transudative chylothorax associated with liver cirrhosis and discuss the common findings associated with chylothoraces.